THE EFFECT OF MIND MAPPING TECHNIQUE ON LEARNING MOTIVATION OF EFL LEARNERS - Indani, Nirfa; Sakkir, Geminastiti; G, Hasriani (Universitas Negeri Makassar, 2025)
This study aims to examine the improvement of learning motivation in students after the application of the mind mapping technique. The researcher applied a pre-experimental method, and to achieve the research objectives, data collection was conducted through a pre-test, post-test, and questionnaire. The population in this study was 11th-grade students at SMPN 1 Tellu Limpoe, and the sample consisted of 30 students determined using the cluster random sampling technique. The research results show that: ) The impact of the mind mapping technique on learning motivation after the same test, namely the T-test, shows a probability value of 0.001 significantly lower than the significance level (0.05), and after being analyzed with N-Gain, shows that the increase in student learning motivation is classified as an increase with a percentage increase of 27.71%. It can be concluded that the use of the mind mapping technique has a significant impact on learning motivation in students.